2018
DOI: 10.1111/jir.12543
|View full text |Cite
|
Sign up to set email alerts
|

The exercise of human rights and citizenship by older adults with an intellectual disability in Ireland

Abstract: Low rates of participation reported here impinge on the rights of older adults with ID under the principles of the UN CRPD. Choice-making emerged as a multi-factorial phenomenon, with different factors important depending on the type of choice involved. This encourages a nuanced and personalised response from policy and support services to overcome individual challenges to participation as equal citizens. The significance of respondent type also highlights the difficulty of including self-report, supported and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
(65 reference statements)
1
15
0
Order By: Relevance
“…The influence of family, particularly parents, on the choices and choice‐making opportunities of adults with intellectual disability, has been identified in a number of recent studies (Biswas, Tickle, Golijani‐Moghaddam, & Almack, ; Caouette, Lachapelle, Moreau, & Lussier‐Desrochers, ; McCausland, McCallion, Brennan, & McCarron, ; Reindl, Waltz, & Schippers, ). While adults with intellectual disability may at times need help with choice and decision making, parents often find it difficult to know when to intervene (Saaltink, MacKinnon, Owen, & Tardif‐Williams, ).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of family, particularly parents, on the choices and choice‐making opportunities of adults with intellectual disability, has been identified in a number of recent studies (Biswas, Tickle, Golijani‐Moghaddam, & Almack, ; Caouette, Lachapelle, Moreau, & Lussier‐Desrochers, ; McCausland, McCallion, Brennan, & McCarron, ; Reindl, Waltz, & Schippers, ). While adults with intellectual disability may at times need help with choice and decision making, parents often find it difficult to know when to intervene (Saaltink, MacKinnon, Owen, & Tardif‐Williams, ).…”
Section: Introductionmentioning
confidence: 99%
“…Authors have suggested that social networks and community participation were associated with voting for people with and without IDD (Campbell, 2013;Kjellberg & Hemmingsson, 2013;Leighly, 1995;McCausland et al, 2018;Schur et al, 2017). Campbell (2013) suggested that voluntary organizations, especially religious organizations, promoted voting among the general population by offering more opportunities for political talk, enforcing social norms of voting, and increasing members' motivation to vote.…”
Section: Participationmentioning
confidence: 99%
“…Among people with IDD, an individual's level of disability has been reported as a significant predictor of voting (Friedman & Rizzolo, 2017). Studies have found that people with more functional limitations, including higher support needs for activities of daily living (ADLs), difficulty communicating verbally, and limited literacy skills were less likely to vote than people without these challenges (Friedman & Rizzolo, 2017;McCausland et al, 2018). The 2017-2018 National Core Indicators In-Person Survey (NCI-IPS) revealed stark differences in voting opportunity by level of intellectual disability.…”
mentioning
confidence: 99%
“…Multiple factors from the personal to the environmental and macro-level variables influence the degree of friendship, inclusion and participation for people with ID (Gauthier-Boudreault et al, 2019;McCausland et al, 2016McCausland et al, , 2016aSimplican et al, 2015). For example, having non-resident friends was associated with people with ID exercising more choice in everyday and key life decisions (McCausland et al, 2018a). People in competitive and supported employment were more likely to have (non-staff and non-family) friends than those in segregated occupational settings (Friedman & Rizzolo, 2018).…”
Section: Factors Associated With Friendshipmentioning
confidence: 99%